SARS-CoV-2 infection of endothelial cells, dependent on flow-induced ACE2 expression, drives hypercytokinemia in a vascularized microphysiological system - Christopher J. Hatch; Sebastian D. Piombo; Jennifer S. Fang; Johannes S. Gach; Makena L. Ewald; William K. Van Trigt; Brian G. Coon; Brian G. Coon; Jay M. Tong; Donald N. Forthal; Donald N. Forthal; Christopher C. W. Hughes; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for COVID-19, has caused nearly 7 million deaths worldwide. Severe cases are marked by an aggressive inflammatory response known as hypercytokinemia, contributing to endothelial damage. Although vaccination has reduced hospitalizations, hypercytokinemia persists in breakthrough infections, emphasizing the need for disease models mimicking this response. Using a 3D microphysiological system (MPS), we explored the vascular role in SARS-CoV-2-induced hypercytokinemia.MethodsThe vascularized micro-organ (VMO) MPS, consisting of human-derived primary endothelial cells (ECs) and stromal cells within an extracellular matrix, was used to model SARS-CoV-2 infection. A non-replicative pseudotyped virus fused to GFP was employed, allowing visualization of viral entry into human ECs under physiologic flow conditions. Expression of ACE2, TMPRSS2, and AGTR1 was analyzed, and the impact of viral infection on ACE2 expression, vascular inflammation, and vascular morphology was assessed.ResultsThe VMO platform facilitated the study of COVID-19 vasculature infection, revealing that ACE2 expression increased significantly in direct response to shear stress, thereby enhancing susceptibility to infection by pseudotyped SARS-CoV-2. Infected ECs secreted pro-inflammatory cytokines, including IL-6 along with coagulation factors. Cytokines released by infected cells were able to activate downstream, non-infected EC, providing an amplification mechanism for inflammation and coagulopathy.DiscussionOur findings highlight the crucial role of vasculature in COVID-19 pathogenesis, emphasizing the significance of flow-induced ACE2 expression and subsequent inflammatory responses. The VMO provides a valuable tool for studying SARS-CoV-2 infection dynamics and evaluating potential therapeutics.